Ethnic families in America patterns and variations - Mindel, Charles H.; Habenstein, Robert Wesley 1914-; Wright, Roosevelt (Prentice Hall, 1998)
This enlightening study offers an inclusive approach to multi-cultural diversity in the U.S, with extensive coverage of the family life styles, traditions and values of seventeen American ethnic groups. Providing unique and personal insights, each chapter is written by a contributing author representing a particular ethnic group, and structured in a similar pattern - covering the historical background, key ethnic cultural components, traditional and current ethnic family characteristics, and changes and adaptations to the ethnic family and culture. Updating statistical information and changes in the ethnic family and culture throughout, the book looks at the differences between ethnic characteristics and other forces impinging upon minority members' lives - such as economics, social class, and social mobility.